QARAQALPAQ TILINDEGI REŃ KOMPONENTLI FRAZEOLOGIZMLERDIŃ LINGVOKULTUROLOGIYALÍQ ÓZGEShELIKLERI - Begniyazova, G. (SCIENCE and SOCIETY, 2025)
This article is about phraseological units with a color component. It will be said that the study of color component phraseology, which is a lexical unit in Karakalpak linguistics, and their lexical-semantic structure, is one of the important features that show the richness of the language’s vocabulary. Also, the direct connection of phraseology with a number of departments of linguistics, including lexicology, stylistics, semantics, etymology, morphology and grammar will be covered.